Impaired facial expression recognition in children with temporal lobe epilepsy: Impact of early seizure onset on fear recognition - Golouboff, Nathalie; Fiori, Nicole; Delalande, Olivier; Fohlen, Martine; Dellatolas, Georges; Jambaqué, Isabelle (Neuropsychologia, 2008)
The amygdala has been implicated in the recognition of facial emotions, especially fearful expressions, in adults with early-onset right temporal lobe epilepsy (TLE). The present study investigates the recognition of facial emotions in children and adolescents, 8–16 years old, with epilepsy. Twenty-nine subjects had TLE (13 right, 16 left) and eight had fronto-central epilepsy (FCE). Each was matched on age and gender with a control subject. Subjects were asked to label the emotions expressed in pictures of children's faces miming five basic emotions (happiness, sadness, fear, disgust and anger) or neutrality (no emotion). All groups of children with epilepsy performed less well than controls. Patterns of impairment differed according to the topography of the epilepsy: the left-TLE (LTLE) group was impaired in recognizing fear and neutrality, the right-TLE (RTLE) group was impaired in recognizing disgust and, the FCE group was impaired in recognizing happiness. We clearly demonstrated that early seizure onset is associated with poor recognition of facial expression of emotion in TLE group, particularly for fear. Although right-TLE and left-TLE subjects were both impaired in the recognition of facial emotion, their psychosocial adjustment, as measured by the CBCL questionnaire [Achenbach, T. M. (1991). Manual for the Child Behavior Checklist and Youth Self-report. Burlington, VT: University of Vermont Department of Psychiatry], showed that poor recognition of fearful expressions was related to behavioral disorders only in children with right-TLE. Our study demonstrates for the first time that early-onset TLE can compromise the development of recognizing facial expressions of emotion in children and adolescents and suggests a link between impaired fear recognition and behavioral disorders.